Lumican accumulates with fibrillar collagen in fibrosis in hypertrophic cardiomyopathy. (29th November 2022) - Rixon, Chloe; Andreassen, Kristine; Shen, Xin; Erusappan, Pugazendhi Murugan; Almaas, Vibeke Marie; Palmero, Sheryl; Dahl, Christen Peder; Ueland, Thor; Sjaastad, Ivar; Louch, William Edward; Stokke, Mathis Korseberg; Tønnessen, Theis; et al.
Abstract: Aims: Familial hypertrophic cardiomyopathy (HCM) is the most common form of inherited cardiac disease. It is characterized by myocardial hypertrophy and diastolic dysfunction, and can lead to severe heart failure, arrhythmias, and sudden cardiac death. Cardiac fibrosis, defined by excessive accumulation of extracellular matrix (ECM) components, is central to the pathophysiology of HCM. The ECM proteoglycan lumican is increased during heart failure and cardiac fibrosis, including HCM, yet its role in HCM remains unknown. We provide an in‐depth assessment of lumican in clinical and experimental HCM. Methods: Left ventricular (LV) myectomy specimens were collected from patients with hypertrophic obstructive cardiomyopathy ( n = 15), and controls from hearts deemed unsuitable for transplantation ( n = 8). Hearts were harvested from a mouse model of HCM; Myh6 R403Q mice administered cyclosporine A and wild‐type littermates ( n = 8–10). LV tissues were analysed for mRNA and protein expression. Patient myectomy or mouse mid‐ventricular sections were imaged using confocal microscopy, direct stochastic optical reconstruction microscopy (dSTORM), or electron microscopy. Human foetal cardiac fibroblasts (hfCFBs) were treated with recombinant human lumican ( n = 3) and examined using confocal microscopy. Results: Lumican mRNA was increased threefold in HCM patients ( P < 0.05) and correlated strongly with expression of collagen I (R 2 = 0.60, P < 0.01) and III (R 2 = 0.58, P < 0.01). Lumican protein was increased by 40% in patients with HCM ( P < 0.01) and correlated with total (R 2 = 0.28, P = 0.05) and interstitial (R 2 = 0.30, P < 0.05) fibrosis. In mice with HCM, lumican mRNA increased fourfold ( P < 0.001), and lumican protein increased 20‐fold ( P < 0.001) in insoluble ECM lysates. Lumican and fibrillar collagen were located together throughout fibrotic areas in HCM patient tissue, with increased co‐localization measured in patients and mice with HCM (patients: +19%, P < 0.01; mice: +13%, P < 0.01). dSTORM super‐resolution microscopy was utilized to image interstitial ECM which had yet to undergo overt fibrotic remodelling. In these interstitial areas, collagen I deposits located closer to (−15 nm, P < 0.05), overlapped more frequently with (+7.3%, P < 0.05) and to a larger degree with (+5.6%, P < 0.05) lumican in HCM. Collagen fibrils in such deposits were visualized using electron microscopy. The effect of lumican on collagen fibre formation was demonstrated by adding lumican to hfCFB cultures, resulting in thicker (+53.8 nm, P < 0.001), longer (+345.9 nm, P < 0.001), and fewer (−8.9%, P < 0.001) collagen fibres. Conclusions: The ECM proteoglycan lumican is increased in HCM and co‐localizes with fibrillar collagen throughout areas of fibrosis in HCM. Our data suggest that lumican may promote formation of thicker collagen fibres in HCM.